Household Salt consumption and urinary iodine levels in Schoolchildren aged 8–10 in Darab City, Iran: 2022 - Sakineh Hooshmand; Fatemeh Yousefian; Habibollah Rahimi; Mahdiyeh Mohammadzadeh; Rouhullah Dehghani (Scientific Reports)
Abstract Iodized salt serves as an effective intervention strategy, combating iodine deficiency disorders (IDD) and promoting overall health. This study aimed to assess the household salt consumption status and its relationship with urinary iodine (UI) levels among school-aged children. This is a descriptive-cross-sectional study that was selected by cluster-random sampling from 5 girls’ schools (182) and 5 boys’ schools (169), with a total of 351 primary school students (8–10 years old) of Darab. To explore the relationship between independent variables and dependent variable, urinary iodine (UI) levels, linear regression model was applied. A significance level of 0.05 was adopted for all analyses. The median UI level was 138 µg/L (IQR = 111). Our findings revealed that 66% of used iodized salt. A significant majority of participants properly stored their salt in containers with lids. Nearly half of the students in Darab have insufficient iodine intake. Despite controlling for the effect of iodized foods consumption, no significant association (P-value = 0.693) was observed between the storage method and iodized foods. Our study showed that students do not receive enough iodine or have received more than the required amount of iodine. Therefore, efforts should be focused on increasing awareness of diseases caused by iodine deficiency.